Preparation method of sulfur-doped amorphous carbon nanosheet and application of sulfur-doped amorphous carbon nanosheet to negative electrode of sodium-ion battery
Through the preparation and application of sulfur-doped amorphous carbon nanosheets, the problem of insufficient performance of negative electrode materials in sodium ion batteries is solved, and high capacity and high magnification battery performance is achieved.
Patent Information
- Application Number
- CN202510256640.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-05
AI Technical Summary
In existing sodium ion batteries, graphite negative electrode materials are difficult to apply, and the rate performance of amorphous carbon materials is insufficient, making it difficult to meet the needs of high capacity and high magnification.
Sulfur-doped amorphous carbon nanosheets were used as the negative electrode material, and sulfur-doped amorphous carbon nanosheets with three-dimensional porous structures were prepared by pre-carbonization of sodium citrate and sulfur doping treatment, and applied to the negative electrode of sodium ion battery.
The specific capacity and rate performance of sodium ion batteries are improved, the conductivity and number of active sites of the material are enhanced, and the performance of high capacity and rate of battery performance is achieved.
Smart Images

Figure CN119750555A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials and relates to the preparation of carbon nanosheets, and in particular to a method for preparing sulfur-doped amorphous carbon nanosheets and application of the same in a negative electrode of a sodium ion battery. Background Art
[0002] For many years, lithium-ion batteries have dominated commercial energy storage devices. However, due to the limited reserves of precursor elements such as lithium, cobalt, nickel and copper required in the production of lithium-ion batteries, the cost and output of lithium-ion batteries are difficult to meet the large-scale energy storage applications in the future. Therefore, sodium-ion batteries have attracted widespread attention due to their abundant natural resources and have become an excellent alternative to lithium-ion batteries.
[0003] Since sodium ions have a larger ionic radius than lithium ions, graphite negative electrode materials widely used in lithium-ion batteries are difficult to use in sodium-ion batteries. So far, most studies have focused on amorphous carbon materials. In principle, the specific capacity of negative electrode carbon materials mainly comes from the surface capacitance control capacity and diffusion control capacity of the bulk phase. However, heteroatom doping is a general method to improve the rate performance of various negative electrode carbon materials for sodium-ion batteries due to the expansion of interlayer spacing and the enhancement of pseudocapacitance. Sulfur doping of carbon materials can not only expand the interlayer spacing of carbon materials, facilitate the insertion and extraction of sodium ions, and improve the rapid kinetics of sodium ions, but also effectively improve the conductivity of the material. In addition, the polysulfides generated by sulfur doping can further increase the number of active sites of carbon materials, thereby improving the specific capacity of sodium-ion batteries.
[0004] The main types of electrolytes commonly used in batteries at present are ester electrolytes and ether electrolytes. Among them, ether electrolytes can form a thinner, denser and more uniform SEI film on the surface of the negative electrode material than ester electrolytes. While improving the interfacial stability of the negative electrode material, ether electrolytes also produce a special ion co-embedding phenomenon compared to ester electrolytes: during the charge and discharge of ether electrolytes, ether solvent molecules will undergo solvation with sodium ions and de-embed into the electrode material together; causing further expansion and contraction of the electrode material, so that the active sites deep in the material are utilized, thereby increasing the reversible capacity of the battery to a certain extent. As a result, the material maintains stability after deep charge and discharge, while the capacity is gradually increasing, showing a rare self-optimization phenomenon. Summary of the invention
[0005] In view of the problems existing in the prior art, the first object of the present invention is to provide a method for preparing sulfur-doped amorphous carbon nanosheets.
[0006] Technical Solution
[0007] A method for preparing sulfur-doped amorphous carbon nanosheets comprises the following steps:
[0008] A. Using sodium citrate as a carbon source, pre-carbonizing in a high-temperature inert atmosphere furnace to obtain a carbon-encapsulated Na2CO3 particle matrix, acid-washing and drying to obtain precursor A;
[0009] B. After the precursor A is fully mixed with the sublimed sulfur, it is placed in a high-temperature inert atmosphere furnace for high-temperature treatment, taken out and naturally cooled to obtain sulfur-doped nanocarbon nanosheets.
[0010] According to a preferred embodiment of the present invention, in step A, the temperature of the pre-carbonization treatment is 400-1000°C, the heat treatment time is 1-5h, the heating rate is 5°C / min, and the inert atmosphere is high-purity nitrogen with a purity of 99.999%; preferably, the temperature is 600°C and the time is 5h.
[0011] In a preferred disclosed example of the present invention, in step A, the acid washing and drying is performed by stirring and washing with a 2M hydrochloric acid solution and then centrifuging and washing with deionized water, and drying at 105° C. for 12 hours to obtain a precursor A.
[0012] According to a preferred embodiment of the present invention, in step B, the precursor A and the sublimated sulfur are mixed at a mass ratio of 1:1 to 10, preferably 1:5, and are fully mixed in a ball mill.
[0013] According to a preferred embodiment of the present invention, in step B, the temperature of the high temperature treatment is 300-600°C, the treatment time is 1-5h, the heating rate is 2°C / min, and the inert atmosphere is high-purity nitrogen with a purity of 99.999%; preferably 400°C and the treatment time is 2h.
[0014] The sulfur-doped amorphous carbon nanosheets prepared according to the method disclosed in the present invention present a three-dimensional porous structure, such as Figure 2 As shown in the scanning electron microscope image, ultra-thin, curved carbon sheets were obtained, which were interconnected and integrated into a 3D foam-like structure; the transmission electron microscope image further showed that the material's macroporous skeleton has abundant supporting cavities.
[0015] The second object of the present invention is to disclose the application of the prepared sulfur-doped amorphous carbon nanosheets, that is, to apply them to the negative electrode of a sodium ion battery.
[0016] A method for preparing a sulfur-doped amorphous carbon negative electrode sheet for a sodium ion battery comprises the following steps:
[0017] S1: premixing sulfur-doped amorphous carbon nanosheet powder, a conductive aid and a binder, adding deionized water and stirring evenly to prepare a negative electrode slurry, wherein, by weight, it includes 8 parts of sulfur-doped amorphous carbon nanosheet powder, 1 part of conductive aid and 1 part of binder;
[0018] S2: Apply the negative electrode slurry on the surface of the copper foil and dry it in vacuum.
[0019] The third object of the present invention is to disclose a sodium ion battery using a sulfur-doped amorphous carbon negative electrode sheet, comprising a positive electrode sheet, a negative electrode sheet, a battery separator and an ether electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, a conductive agent and a binder, and the positive electrode active material comprises any one or more of layered oxides, polyanions and Prussian blue;
[0020] The battery separator is polyethylene, polypropylene, glass fiber separator or polytetrafluoroethylene;
[0021] The solvent of the ether electrolyte is one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and dioxolane; the salt is one or more of NaPF6, NaClO4, and the like.
[0022] Beneficial Effects
[0023] The invention discloses a sulfur-doped amorphous carbon negative electrode material and a preparation method of a corresponding negative electrode sheet and a sodium ion battery, wherein the stacking of sulfur-doped nanocarbon sheets presents a three-dimensional porous structure, which is expected to expand the surface area of the electrode / electrolyte for ion insertion and adsorption; and the sulfur dopant and the small polysulfide aggregates make the sulfur-doped carbon nanosheets have more active sites and wider interlayer spacing, which is conducive to the rapid storage and diffusion of ions and improves the rapid dynamics of the sodium ion battery; in addition, the sulfur-doped nanocarbon sheet has a simple process and low cost, and can be used as a negative electrode material for sodium ion batteries in sodium ion batteries, so that the sodium ion battery has excellent performance such as high capacity and high rate performance. After the material is made into a negative electrode sheet, it is prepared into a sodium ion battery with an ether electrolyte, and the stability of the solid electrolyte interface film of the sodium ion battery can be improved through co-embedding, and excellent cycle performance can be obtained; at the same time, the polysulfide generated by the sulfur doped in the carbon material after annealing will be further effectively activated by the ether electrolyte, especially at high current density, thereby improving the rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 . Flow chart of the preparation method of sulfur-doped amorphous carbon nanosheets and their precursor A;
[0025] Figure 2 The scanning electron microscope images and projection electron microscope images of the precursor A and the sulfur-doped amorphous carbon nanosheets prepared in Example 1 and the EDS elemental images of sulfur-doped amorphous carbon about C, O, and S, the mass percentages of which are 82.67%, 4.79%, and 12.54%, respectively;
[0026] Figure 3 Comparison of cyclic voltammetry curves of sulfur-doped amorphous carbon nanosheets prepared in Example 1 respectively adapted to ether electrolyte DME and ester electrolyte EC / PC at low scan rate;
[0027] Figure 4 Comparison of current charge and discharge of sulfur-doped amorphous carbon nanosheets prepared in Example 1 with different cycles of current at lower current density using ether electrolyte DME and ester electrolyte EC / PC;
[0028] Figure 5 . Comparison of rate performance of sulfur-doped amorphous carbon nanosheets prepared in Example 1 in ether electrolyte DME and ester electrolyte EC / PC under step current density. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. In addition, in the description of this application, the term "including" means "including but not limited to".
[0030] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0031] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0032] Example 1
[0033] A method for preparing sulfur-doped amorphous carbon nanosheets comprises the following steps:
[0034] A. Sodium citrate is used as a carbon source and placed in a high-temperature inert atmosphere furnace for pre-carbonization treatment to obtain a carbon-encapsulated Na2CO3 particle matrix, the carbon-encapsulated Na2CO3 particle matrix is stirred and washed with a 2M hydrochloric acid solution for 12 hours, and then thoroughly washed and centrifuged with deionized water for more than three times, and the obtained sample is dried in a blast drying oven at 105°C for 12 hours to obtain a precursor A; wherein the pre-carbonization temperature is 600°C, the heat treatment time is 5 hours, the heating rate is 5°C / min, and the inert atmosphere is high-purity nitrogen with a purity of 99.999%;
[0035] B. The precursor A and sublimed sulfur are fully mixed in a ball mill at a mass ratio of 1:5, and the mixture is placed in a high-temperature inert atmosphere furnace at a temperature of 400° C., a heat treatment time of 2 h, a heating rate of 2° C. / min, and an inert atmosphere of high-purity nitrogen with a purity of 99.999%, to obtain sulfur-doped amorphous carbon nanosheets.
[0036] In an inert atmosphere glove box with water / oxygen indicators <0.1ppm, the prepared sulfur-doped amorphous carbon nanosheet powder was used as the negative electrode material to prepare a sodium ion battery. Glass fiber was used as the separator. CR2032 button cells were assembled in the order of positive electrode shell-sulfur-doped amorphous carbon-glass fiber separator-ether electrolyte ethylene glycol dimethyl ether (DME)-sodium sheet-gasket-spring sheet-negative electrode shell and the electrochemical performance was tested.
[0037] The sodium ion batteries assembled with the sulfur-doped amorphous carbon negative electrode sheet and using ethylene glycol dimethyl ether (DME) as the electrolyte were subjected to 0.2 mVs −1 Low scan rate cyclic voltammetry (CV), 100 mAhg -1 Low current density charge-discharge cycle test (GCD) and current density of 0.1, 0.2, 0.5, 1.0, 2.0, 5.0, 10, 20 and 50 Ag -1 The rate performance test is as follows. Figure 3 As shown in Figure 2, sulfur-doped amorphous carbon with ethylene glycol dimethyl ether (DME) exhibits two pairs of redox peaks at 1.9 / 2.2 and 0.8 / 1.7 V. Figure 4 Shown at 100 mAhg -1 In the deep charge-discharge cycle with low current density, the sulfur-doped amorphous carbon material with ethylene glycol dimethyl ether (DME) showed a rare gradual growth trend, and the specific capacity reached 467.2 mAh g after 100 deep cycles. -1 .like Figure 5 As shown, at current densities of 0.1, 0.2, 0.5, 1.0, 2.0, 5.0, 10, 20, and 50 Ag -1When the electrolyte was based on ethylene glycol dimethyl ether (DME), the electrodes provided 437, 434, 414, 398, 376, 337, 305, 270, and 191 mAh g -1 reversible specific capacity.
[0038] In order to further illustrate the key points of the present invention, comparative examples are added for illustration.
[0039] Comparative Example 1
[0040] The sodium ion battery preparation process is basically the same as that of Example 1, wherein the precursor A is retained and sulfur doping is not performed.
[0041] like Figure 2 As shown, by comparing the scanning electron microscope images and transmission electron microscope images of the sulfur-doped amorphous carbon material with the precursor A, it can be seen that both before and after sulfur doping have a similar 3D framework structure composed of ultra-thin spring flakes, indicating that sulfur doping does not change the carbon layer structure.
[0042] Comparative Example 2
[0043] The preparation process of the sodium ion battery is basically the same as that of Example 1, wherein the electrolyte is replaced by an ester electrolyte EC / PC.
[0044] like Figure 3 As shown, at 0.2 mVs −1 In the low-scan rate cyclic voltammetry test (CV), the sulfur-doped amorphous carbon with ester electrolyte EC / PC only showed a pair of redox peaks at 1.77 / 1.69V, and it can be seen that the sulfur-doped amorphous carbon with ethylene glycol dimethyl ether (DME) has a larger area of voltammetry curve, more significant surface redox reaction, and better electrochemical performance. Figure 4 Shown at 100 mAhg -1 In the deep charge-discharge cycle with low current density, the sulfur-doped amorphous carbon material with ester electrolyte EC / PC has a specific capacity of only 331.4 mAh g after 100 deep cycles. -1 After 100 deep cycles, the specific capacity reached 467.2 mAh g -1 .like Figure 5 As shown, at current densities of 0.1, 0.2, 0.5, 1.0, 2.0, 5.0, 10, 20, and 50 A g -1 When the electrolyte is based on ester electrolyte EC / PC, the electrodes can only provide 444, 418, 384, 358, 328, 275, 197, 154 and 82.4 mAh g -1 The reversible specific capacity of Figure 3 , 4 and Figure 5It can be clearly seen that the electrochemical performance of sulfur-doped amorphous carbon materials in ether electrolyte ethylene glycol dimethyl ether (DME) is significantly better than that in ester electrolyte (EC / PC).
[0045] Example 2
[0046] A method for preparing sulfur-doped amorphous carbon nanosheets comprises the following steps:
[0047] A. Sodium citrate is used as a carbon source and placed in a high-temperature inert atmosphere furnace for pre-carbonization treatment to obtain a carbon-encapsulated Na2CO3 particle matrix, the carbon-encapsulated Na2CO3 particle matrix is stirred and washed with a 2M hydrochloric acid solution for 12 hours, and then thoroughly washed and centrifuged with deionized water for more than three times, and the obtained sample is dried in a blast drying oven at 105°C for 12 hours to obtain a precursor A; wherein the pre-carbonization temperature is 1000°C, the heat treatment time is 1 hour, the heating rate is 5°C / min, and the inert atmosphere is high-purity nitrogen with a purity of 99.999%;
[0048] B. The precursor A and sublimed sulfur are fully mixed in a ball mill at a mass ratio of 1:2, and the mixture is placed in a high-temperature inert atmosphere furnace at a temperature of 300° C., a heat treatment time of 2 h, a heating rate of 2° C. / min, and an inert atmosphere of high-purity nitrogen with a purity of 99.999%, to obtain sulfur-doped amorphous carbon nanosheets.
[0049] The obtained sulfur-doped amorphous carbon material was adapted to the ether electrolyte ethylene glycol dimethyl ether (DME) in an inert atmosphere glove box with water / oxygen index <0.1ppm to assemble into a CR2032 button cell. -1 The low current density charge-discharge cycle test (GCD) showed that the specific capacity was only 427 mAh g after 100 deep cycles. -1 .
[0050] Example 3
[0051] A method for preparing sulfur-doped amorphous carbon nanosheets comprises the following steps:
[0052] A. Sodium citrate is used as a carbon source and placed in a high-temperature inert atmosphere furnace for pre-carbonization treatment to obtain a carbon-encapsulated Na2CO3 particle matrix, the carbon-encapsulated Na2CO3 particle matrix is stirred and washed with a 2M hydrochloric acid solution for 12 hours, and then thoroughly washed and centrifuged with deionized water for more than three times, and the obtained sample is dried in a blast drying oven at 105°C for 12 hours to obtain a precursor A; wherein the pre-carbonization temperature is 400°C, the heat treatment time is 5 hours, the heating rate is 5°C / min, and the inert atmosphere is high-purity nitrogen with a purity of 99.999%;
[0053] B. The precursor A and sublimed sulfur are fully mixed in a ball mill at a mass ratio of 1:10, and the mixture is placed in a high-temperature inert atmosphere furnace at a temperature of 600° C., a heat treatment time of 2 h, a heating rate of 2° C. / min, and an inert atmosphere of high-purity nitrogen with a purity of 99.999%, to obtain sulfur-doped amorphous carbon nanosheets.
[0054] The obtained sulfur-doped amorphous carbon material was adapted to the ether electrolyte ethylene glycol dimethyl ether (DME) in an inert atmosphere glove box with water / oxygen indexes < 0.1 ppm to assemble into a CR2032 button cell. -1 The low current density charge-discharge cycle test (GCD) showed that the specific capacity was only 446 mAh g after 100 deep cycles. -1 .
[0055] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing sulfur-doped amorphous carbon nanosheets, characterized in that: The steps include: A. Using sodium citrate as a carbon source, pre-carbonizing in a high-temperature inert atmosphere furnace to obtain a carbon-encapsulated Na2CO3 particle matrix, acid-washing and drying to obtain precursor A; B. After the precursor A is fully mixed with the sublimed sulfur, it is placed in a high-temperature inert atmosphere furnace for high-temperature treatment, taken out and naturally cooled to obtain sulfur-doped nanocarbon nanosheets.
2. The method for preparing sulfur-doped amorphous carbon nanosheets according to claim 1, characterized in that: In step A, the temperature of the pre-carbonization treatment is 400-1000° C., the heat treatment time is 1-5 hours, the heating rate is 5° C. / min, and the inert atmosphere is high-purity nitrogen with a purity of 99.999%.
3. The method for preparing sulfur-doped amorphous carbon nanosheets according to claim 2, characterized in that: In step A, the pre-carbonization treatment is carried out at a temperature of 600° C. for 5 hours.
4. The method for preparing sulfur-doped amorphous carbon nanosheets according to claim 1, characterized in that: In step A, the acid washing and drying is performed by stirring and washing with a 2M hydrochloric acid solution and then centrifuging with deionized water, and drying at 105° C. for 12 h to obtain precursor A.
5. The method for preparing sulfur-doped amorphous carbon nanosheets according to claim 1, characterized in that: In step B, the precursor A and the sublimed sulfur are mixed in a mass ratio of 1:1 to 10 and are fully mixed in a ball mill.
6. The method for preparing sulfur-doped amorphous carbon nanosheets according to claim 5, characterized in that: In step B, the precursor A is mixed with sublimed sulfur in a mass ratio of 1:
5.
7. The method for preparing sulfur-doped amorphous carbon nanosheets according to claim 1, characterized in that: In step B, the temperature of the high temperature treatment is 300-600° C., the treatment time is 1-5 hours, the heating rate is 2° C. / min, and the inert atmosphere is high-purity nitrogen with a purity of 99.999%.
8. The method for preparing sulfur-doped amorphous carbon nanosheets according to claim 7, characterized in that: In step B, the temperature of the high temperature treatment is 400° C. and the treatment time is 2 hours.
9. Sulfur-doped amorphous carbon nanosheets prepared according to the method of any one of claims 1 to 8.
10. An application of the sulfur-doped amorphous carbon nanosheets as claimed in claim 9, characterized in that: It is applied to the negative electrode of sodium-ion batteries.
Citation Information
Patent Citations
Sulfur-doping porous carbon material of sodium ion battery and preparation method of sulfur-doping porous carbon material
CN105810914A
Sulfur-carbon composite, method for producing same, and positive electrode for lithium-sulfur battery and lithium-sulfur battery which comprise same
CN112189269A
Method for preparing oxygen atom-doped three-dimensional porous ultrathin carbon nanosheet
CN114057181A
Sulfur-doped corn silk porous carbon as well as preparation method and application thereof
CN119306203A
Preparation method and application of sulfur-doped metal monatomic loaded porous carbon material
CN119390053A